Association Between Oral Health and General Health Among Adults in Tasikmalaya - Rieza Zulfahmi Taftazani; Lina Rismayani; Emma Kamelia; Eliati Sri Suharja; Anang; Cahyo Nugroho (Media Informasi, 2026)
Background: Oral health is strongly connected to systemic health, yet in many communities it is still underprioritized. Limited awareness and poor oral hygiene practices may contribute to adverse health outcomes.Objective: To examine the relationship between oral health knowledge, dental hygiene behavior, and general health status among adults in Tasikmalaya. Methods: A cross-sectional survey was conducted among 30 adults participating in a community-based mobile education program. Data on oral health knowledge and hygiene behavior were collected via structured questionnaires, while general health indicators (blood pressure, BMI, waist circumference, blood glucose, and cholesterol) were measured directly. Descriptive and bivariate analyses were used to assess associations. Results: Higher oral health knowledge was associated with better hygiene behaviors, including regular toothbrushing and reduced sugary food intake. Poor hygiene practices were linked with higher prevalence of hypertension (32.0%) and elevated cholesterol (36.7%). Additionally, 40.0% of respondents were overweight or obese, and 28.0% had central obesity. These patterns suggest an association between poor oral health behaviors and cardiovascular risk factors. Conclusion: Oral health and general health are interrelated among adults in Tasikmalaya. Strengthening oral health promotion and integrating dental hygiene education into general health programs are recommended to support both oral and systemic health